2017
DOI: 10.3389/fpls.2017.00480
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Identification and Characterization of Apple bHLH Transcription Factors and Expression Analysis in Response to Drought and Salt Stress

Abstract: The bHLH (basic helix-loop-helix) transcription factor family is the second largest in plants. It occurs in all three eukaryotic kingdoms, and plays important roles in regulating growth and development. However, family members have not previously been studied in apple. Here, we identified 188 MdbHLH proteins in apple “Golden Delicious” (Malus × domestica Borkh.), which could be classified into 18 groups. We also investigated the gene structures and 12 conserved motifs in these MdbHLHs. Coupled with expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
167
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(173 citation statements)
references
References 66 publications
5
167
1
Order By: Relevance
“…Network interaction analysis has been demonstrated to be an effective method to analyse the gene function [40]. We used the online software STRING 10 to predict the protein interaction network with the 142 CsbHLH protein sequences as queries, which formed a complex interaction network constructed with orthologs in Arabidopsis.…”
Section: The Protein Interaction Network Predictions For Csbhlh Orthomentioning
confidence: 99%
See 1 more Smart Citation
“…Network interaction analysis has been demonstrated to be an effective method to analyse the gene function [40]. We used the online software STRING 10 to predict the protein interaction network with the 142 CsbHLH protein sequences as queries, which formed a complex interaction network constructed with orthologs in Arabidopsis.…”
Section: The Protein Interaction Network Predictions For Csbhlh Orthomentioning
confidence: 99%
“…The basic helix-loop-helix (bHLH) transcription factor family is the second largest family in eukaryotes [10,44] and extensive studies of bHLH families have been identified in various plants [2]. For example, 166 bHLH genes have been identified in Arabidopsis [2,10], 115 bHLH genes in Nelumbo nucifera [45], 188 bHLH genes in apple [40], 167 bHLH genes in rice [12] and 159 bHLH genes in tomato [13]. The bHLH transcription factors have been involved in multiple biological processes in plants, especially in regulating defense against biotic and abiotic stresses [46].…”
Section: Characterization Of the Cucumber Bhlh Familymentioning
confidence: 99%
“…The protein interaction network predictions for CsbHLH orthologs in Arabidopsis that were crucial for the abiotic stress response Network interaction analysis has been demonstrated to be an effective method to analyse the gene function [40]. We used the software STRING 10 to predict the protein interaction network among the 142 CsbHLH proteins (Fig.…”
Section: Expression Analysis Of Csbhlh Genes Under Different Stress Cmentioning
confidence: 99%
“…The basic helix-loop-helix (bHLH) transcription factor family is the second largest family in eukaryotes [10,44] and extensive studies of bHLH families have been identi ed in various plants [2]. For example, 166 bHLH genes have been identi ed in Arabidopsis [2,10], 115 bHLH genes in Nelumbo nucifera [45], 188 bHLH genes in apple [40], 167 bHLH genes in rice [12] and 159 bHLH genes in tomato [13]. The bHLH TFs have been involved in multiple biological processes in plants, especially in regulating defense against biotic and abiotic stresses [46].…”
Section: Characterization Of the Cucumber Bhlh Familymentioning
confidence: 99%
“…These genes are putative transcription factor bHLH63 (Cc05_g16570) and transcription factor bHLH135 (Cc07_g03240). According to Mao et al (2017), under salt stress condition some special bHLH TFs are activated and bind to the promoter of the key genes involved in various signaling pathways and regulate the stress tolerance of plants by regulating the transcription level of these target genes. In this experiment, two down regulated STP transcription factor genes were significantly expressed under salt stress condition.…”
Section: E-23mentioning
confidence: 99%